2018
DOI: 10.18820/24150525/comm.v23.1
|View full text |Cite
|
Sign up to set email alerts
|

Art or dark art? Moral failure and ethical obligation in South African public relations practice

Abstract: Ethical failures are not just philosophical problems, but also economic problems that hold significant social and political consequences for the social and communal contexts in which these are enacted. Recent ethical scandals such as Bell Pottinger and Cambridge Analytica have reawakened public debate on ethical standards in professional practice. While some research on PR roles has been conducted in the South African context since 2002, there are no formally documented studies regarding the moral philosophy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Technological advancements have forced PR practitioners to reimagine their roles as boundary spanners and develop multiple approaches to deal with challenges and tensions that may arise (Verwey, 2015), such as ethical dilemmas on social media. Hagelstein et al (2021) reported that practitioners today encounter more moral challenges in their day-to-day work than they have before.…”
Section: Pr In Social Media Spaces: Challenges and Ethically Acceptab...mentioning
confidence: 99%
“…Technological advancements have forced PR practitioners to reimagine their roles as boundary spanners and develop multiple approaches to deal with challenges and tensions that may arise (Verwey, 2015), such as ethical dilemmas on social media. Hagelstein et al (2021) reported that practitioners today encounter more moral challenges in their day-to-day work than they have before.…”
Section: Pr In Social Media Spaces: Challenges and Ethically Acceptab...mentioning
confidence: 99%
“…It is evident that going forward, South African public relations and communication practitioners will be required to embrace and expand their boundary spanning roles. This will enable collaboration between variously situated participants from a variety of disciplinary and social, and institutional contexts, and to embrace mechanisms of stakeholder participation which will transform values, practices and institutions through experimentation, social innovation and collaborative learning (Verwey, 2015). It is also evident that current disciplinary boundary-setting practices, and paradigmatic fixation -along with outcomes based pedagogical approaches to PR education in South Africa -do not adequately prepare future practitioners for the possibilities and social consequences of PR practice.…”
Section: Values-based Approach To Pr Educationmentioning
confidence: 99%
“…The literature claims that SCPs are increasingly subjected to 'individual relativism' (Verwey and Muir, 2018). Individual relativism involves establishing personal moral reference points using consistent balancing of their position with organisation requirements, contracted duties and accountability (Verwey and Muir, 2018). The boundary lines are often blurry for SCPs.…”
Section: Communitarian Ethicsmentioning
confidence: 99%
“…It implies redefining roles and acting virtuously based on having a conception of good, personal values on what they identify with and work towards (Verwey et al ., 2017). The literature claims that SCPs are increasingly subjected to ‘individual relativism’ (Verwey and Muir, 2018). Individual relativism involves establishing personal moral reference points using consistent balancing of their position with organisation requirements, contracted duties and accountability (Verwey and Muir, 2018).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%